Ambalat Dispute Settlement Analysis Study: Juridical Review of Regional Conflict Between Indonesia and Malaysia Based on an International Law Perspective - Noer, Rana Tatsbita; Majiid, Karim Abdul (International Law Discourse in Southeast Asia, 2023)
The Ambalat dispute between Indonesia and Malaysia stands as a prominent example of a regional conflict rooted in territorial claims and maritime boundaries. This study conducts a comprehensive juridical review of the Ambalat dispute, focusing on the application of international law principles. Through an examination of relevant treaties, customary international law, and judicial decisions, this analysis aims to provide insights into the legal dimensions of the conflict and potential avenues for its resolution. The study begins by outlining the historical background of the Ambalat dispute, tracing the origins of conflicting claims over the maritime territory. It then proceeds to analyze the legal frameworks governing maritime boundaries, including the United Nations Convention on the Law of the Sea (UNCLOS) and customary international law. Special attention is given to the principles of territorial sovereignty, equitable maritime delimitation, and peaceful dispute settlement mechanisms enshrined in international law. Furthermore, the study evaluates past attempts at resolving the Ambalat dispute, including bilateral negotiations and third-party mediation efforts. By critically assessing the effectiveness of these mechanisms, the study identifies key challenges and opportunities for achieving a durable settlement. Moreover, it examines the role of international organizations and legal forums in facilitating dialogue and promoting compliance with international law. In conclusion, the study offers recommendations for policymakers and stakeholders involved in the Ambalat dispute, emphasizing the importance of adherence to international legal principles and the pursuit of peaceful resolution mechanisms. By fostering a deeper understanding of the legal complexities surrounding the conflict, this analysis seeks to contribute to the advancement of regional stability and cooperation in Southeast Asia.